Typification of the name Litsea mackeei (née Lauraceae) and its reassignment to the synonymy of Osmanthus austrocaledonicus var. austrocaledonicus (Oleaceae) - Munzinger, Jérôme; Mcpherson, Gordon (Phytotaxa, 2017)
The protologue of Litsea mackeei states that its holotype is at P. However, two specimens bearing the type number appear to exist at P, the second specimen belonging to a species different from the first and bearing as well a label with a different collection number. Fortunately, a clear indication of which plant Kostermans was describing is provided by his handwritten annotation of the isotype at L. A lectotype is therefore chosen, the name is synonymized with Osmanthus austrocaledonicus var. austrocaledonicus and the origin of this unlikely error is discussed.